Genetic assessment of captive elephant (Elephas maximus) populations in Thailand - Chatchote Thitaram (2018)
The genetic diversity and population structure of 136 captive Thai elephants (Elephas maximus) with known region of origin were investigated by analysis of 14 highly polymorphic microsatellite loci. We did not detect significant indications of inbreeding and only a low differentiation of elephants from different regions. This is probably explained by the combined effects of isolation by distance and exchange between different regions or between captive and wild elephant populations. Estimates of effective population sizes were in the range of 90-240 individuals, which emphasizes the necessity to guard against inbreeding as caused by the current use of a restricted number of breeding bulls. © Springer Science+Business Media B.V. 2009.